The insulinotropic potency of fatty acids is influenced profoundly by their chain length and degree of saturation. - Stein, D T (1997)
Lowering of the elevated plasma FFA concentration in 18- 24-h fasted rats with nicotinic acid (NA) caused complete ablation of subsequent glucose-stimulated insulin secretion (GSIS). Although the effect of NA was reversed when the fasting level of total FFA was maintained by coinfusion of soybean oil or lard oil (plus heparin), the more saturated animal fat proved to be far more potent in enhancing GSIS. We therefore examined the influence of individual fatty acids on insulin secretion in the perfused rat pancreas. When present in the perfusion fluid at 0.5 mM (in the context of 1% albumin), the fold stimulation of insulin release from the fasted pancreas in response to 12.5 mM glucose was as follows: octanoate (C8:0), 3.4; linoleate (C18:2 cis/cis), 5.3; oleate (C18:1 cis), 9.4; palmitate (C16:0), 16. 2; and stearate (C18:0), 21.0. The equivalent value for palmitoleate (C16:1 cis) was 3.1. A cis--> trans switch of the double bond in the C16:1 and C18:1 fatty acids had only a modest, if any, impact on their potency. A similar profile emerged with regard to basal insulin secretion (3 mM glucose). When a subset of these fatty acids was tested in pancreases from fed animals, the same rank order of effectiveness at both basal and stimulatory levels of glucose was seen. The findings reaffirm the essentiality of an elevated plasma FFA concentration for GSIS in the fasted rat. They also show, however, that the insulinotropic effect of individual fatty acids spans a remarkably broad range, increasing and decreasing dramatically with chain length and degree of unsaturation, respectively. Thus, for any given level of glucose, insulin secretion will be influenced greatly not only by the combined concentration of all circulating (unbound) FFA, but also by the makeup of this FFA pool. Both factors will likely be important considerations in understanding the complex interplay between the nature of dietary fat and whole body insulin, glucose, and lipid dynamics.